Leading patent breadth, endogenous quality choice, and economic growth - Keishun Suzuki; Shin Kishimoto (Osaka University, Institute of Social and Economic Research (ISER), 2023)
O'donoghue and Zweimüller (2004, J. of Econ. Growth), a seminal work, showed that broadening leading breadth in patent protection can stimulate innovation. However, the empirical literature has consistently found skeptical results on the positive effect. To fill the gap, we build another framework where the quality improvement size is derived as an interior solution. In our model, broadening leading breadth can negatively affect innovation because each innovator is incentivized to free-ride the other innovators' quality improvements. As a further analysis, we quantitatively investigate the growth effect of intervention in patent licensing negotiation using two different profit division rules derived from a cooperative game. We find that intervention in patent licensing negotiation increases the growth rate and stabilizes the economy.
Keywords: C71; D45; O30; 330; Patent protection; Leading breadth; Schumpeterian growth; Endogenous qualityincrements; Cooperative game